Influence of various commercially available organic manures on growth, yield and nutrient accumulation in mint plants (Mentha sp.) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
A pot experiment was set up using completely randomized design (CRD) to compare the influences of different commonly available organic manures in the markets of Dhaka, Bangladesh on the growth parameters and nutrient contents in Mint plants (Mentha sp.). Eight different manures were used as treatments for the comparison, viz. ACI, Alo, Annopurna Vermicompost, Cow dung, Kazi, Mazim, Modern Vermicompost and Trichocompost GBD, along with a control, taking three replications of each treatment. After 2.5 months (75 days) the plants were harvested. Trichocompost GBD showed the highest average number of leaves (130.33 plant-1), plant height (27.67 cm plant-1), number of branches (11.00 plant-1) and number of stolons at harvest (1.67 plant-1). The maximum average single leaf area (2.01 cm2 plant-1) and fresh weight (1.68 g plant-1) were observed in Kazi. ACI was observed to have the highest dry weight (0.26 g plant-1), whereas cow dung had the longest root (8.57 cm plant-1). Nutrient accumulation in leaf and stem exhibited the highest N in ACI, highest P and K in Alo, and highest S in Kazi. Correlation analysis of the explored traits with nutrient concentration of plant shoots was performed to elucidate the impact of plant nutrient contents on the analysed parameters.J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(1): 73-84